Akbar Gadget / Muhammad Muizzuddin Azizan - Azizan, Muhammad Muizzuddin (Faculty of Business and Management, 2023)
My unforgettable and interesting six months industrial training began here at Akbar Gadget. My name is Muhammad Muizzuddin bin Azizan and I have been assigned at marketing department as I must make any content and post ad media social such as TikTok, Facebook, YouTube and Instagram. Akbar Gadget is a company focuses on repairing phone and sell anything related to phone and this company located at Balok Center, Kuantan, Pahang. The vision of this company is to be gadget and accessories shop number one in Pahang. This company’s mission is to strengthen and enhance development and management activities so that this company can enhance and boost Bumiputera equity and ensure the profitability of the company. This company have two branch which is first branch located at Balok Makmur and second branch located at Balok Center Kuantan, Pahang. I also provide SWOT analysis in this report. Under SWOT analysis, the strength that this company has is that this company have very strategic location and was a well-known company around the Balok area, so this company also have great reputation among the customer. Using old technology in closing system is one of the weaknesses of this company. So, in order to fix this weakness, I recommend the company to buy new software and casher machine to automatically calculate the daily closing. Next, there are external factor which one of them is trend were consumer focus on environmental sustainability can give Akbar Gadget an opportunity to increase their profit and business awareness. Lastly is threat, there are many competitors within the company target area which can interrupt the company business. The competitor also has the same business which is phone repair shop, so this can reduce the Akbar Gadget profit.